Burnout among forensic interviewers, how they cope, and what agencies can do to help - Fansher, Ashley K. (Child maltreatment, 2020)
The current study used quantitative and qualitative responses from 250 forensic interviewers (FIs) in the United States to examine predictors of burnout and personal coping mechanisms. Findings indicated that burnout was primarily driven by work-related factors including frequently feeling overwhelmed with job-related duties, inadequate organizational support, and direct exposure to graphic materials involving children. Moreover, having a higher degree of compassion satisfaction and being non-White significantly mitigated symptoms of burnout. Qualitative findings indicated that FIs regularly experienced varied and personalized feelings of burnout and utilized a variety of coping methods to combat their stressors. FIs in this study also made individual suggestions regarding how their respective agencies can assist in the coping process. Policy implications are discussed.